2008
DOI: 10.1111/j.1553-2712.2008.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study of Wound Bursting Strength and Compliance of Topical Skin Adhesives

Abstract: Objectives: Over the past decade, the use of topical skin adhesives (TSA) for wound closure has increased. Among TSA characteristics, strength and flexibility are most important. Prior studies have compared the wound bursting strengths (WBSs) of the cyanoacrylates immediately after wound closure. In this study the authors compared the WBS and flexibility of multiple TSAs immediately and up to 2 days after closure.Methods: This was a controlled animal experiment. Two-centimeter incisions were created on both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Previous biomechanical studies have used "loose skin" animal models, including the rat and guinea pig. [3][4][5] However, the structure of skin in these animals is unlike that of humans, and in particular, the presence of the underlying paniculus carnosa and the loose skin result in rapid and tension-free healing in these small animals. In contrast, the skin of pigs is thicker and, like in humans, does not contain the paniculus carnosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous biomechanical studies have used "loose skin" animal models, including the rat and guinea pig. [3][4][5] However, the structure of skin in these animals is unlike that of humans, and in particular, the presence of the underlying paniculus carnosa and the loose skin result in rapid and tension-free healing in these small animals. In contrast, the skin of pigs is thicker and, like in humans, does not contain the paniculus carnosa.…”
Section: Discussionmentioning
confidence: 99%
“…However, several prior studies have already reported the bursting strength using this adhesive. 4,5 Finally, while we have noted considerable differences among the studied TSA, the differences among the various commercially available skin adhesives might not have any clinically relevant effect on outcomes of wound care.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic outcome of a study published by Singer et al [25] was that among tested glues the octylcyanoacrylate tissue adhesive is the strongest and most flexible glue. Nevertheless, the principal limitation of those studies is that the wound properties were measured just up to 2 days after closure.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the wound-breaking strengths after wound closure with a tissue adhesive based on cyanoacrylate either immediately after closure or 1 and 2 days after wounding were evaluated [21,25] . The basic outcome of a study published by Singer et al [25] was that among tested glues the octylcyanoacrylate tissue adhesive is the strongest and most flexible glue.…”
Section: Discussionmentioning
confidence: 99%